Prevalence, predictive factors and clinical course of persistent pain associated with teeth displaying periapical healing following nonsurgical root canal treatment: a prospective study. (9th November 2018) - Philpott, R.; Gulabivala, K.; Leeson, R.; Ng, Y.‐L.
Abstract: Aims: To investigate the prevalence, pain catastrophizing and other predictive factors and clinical course of persistent pain/discomfort associated with teeth displaying periapical healing following nonsurgical root canal treatment (NSRCT). Methodology: One hundred and ninety‐eight patients (264 teeth) who had NSRCT were reviewed at 5–14 months, postoperatively. Teeth with persistent post‐treatment pain or discomfort, plus evidence of periapical healing were further monitored 0.5, 4 and 10 years later. Pain Catastrophizing Scale (PCS) and Short Form of the McGill Pain Questionnaire (SF‐MPQ) were completed. Predictive factors were investigated using logistic regression models. Results: Twenty‐four per cent (60/249) of teeth displaying periapical healing at first review were associated with persistent pain or discomfort. Fifty‐five teeth monitored 6–7 months later were associated with reduction in pain (17/30) or discomfort (7/25). Cone beam computed tomography (CBCT) of eight teeth with persistent symptoms and complete periapical healing (by conventional radiographs) revealed distinct, small apical radiolucencies ( n = 3) or root apex fenestration through the buccal plate ( n = 2). History of chronic pain (headache, temporo‐mandibular joint, masticatory muscle, neck, shoulder or back pain; P = 0.005), preoperative pain ( P = 0.04), responsive pulp ( P = 0.009), tooth crack ( P = 0.05) and small periapical radiolucency ( P = 0.005) were significant predictive factors. The PCS revealed 16 patients (22 teeth) were catastrophizers (PCS ≥ 30), but this had no influence on post‐treatment symptoms ( P = 0.5). Conclusions: Persistent pain or discomfort associated with teeth showing periapical healing at the first review after NSRCT, decreased in intensity in most cases over the following 6 months. Longer‐term follow‐up revealed spontaneous improvement or symptom resolution in the majority of those with confirmed radiographic the absence of periapical disease. Five predictive factors (history of chronic pain, teeth with responsive pulps, association with pain, diagnosis of tooth crack before treatment and diameter of preoperative radiolucency) were identified.